Effects of dietary fat on insulin secretion in subjects with the metabolic syndrome. Issue 5 (May 2019) - Gulseth, Hanne L; Gjelstad, Ingrid M F; Tiereny, Audrey C; McCarthy, Danielle; Lovegrove, Julie A; Defoort, Catherine; Blaak, Ellen E; Lopez-Miranda, Jose; Dembinska-Kiec, Aldona; Risérus, Ulf; Roche, Helen M; Drevon, Christian A; et al.
Abstract : Objective: Impaired insulin secretion and action contribute to the development of type 2 diabetes. Dietary fat modification may improve insulin sensitivity, whereas the effect on insulin secretion is unclear. We investigated the effect of dietary fat modification on insulin secretion in subjects with the metabolic syndrome. Design: In a 12-week pan-European parallel, randomized controlled dietary intervention trial (LIPGENE), 486 subjects were assigned to four isoenergetic diets: high-fat diets rich in saturated fat (HSFA) or monounsaturated fat (HMUFA) or low-fat, high-complex carbohydrate diets with (LFHCC n- 3) or without (LFHCC control) 1.2 g/day of n -3 PUFA supplementation. Insulin secretion was estimated as acute insulin response to glucose (AIRg) and disposition index (DI), modeled from an intravenous glucose tolerance test. Results: There were no overall effect of the dietary intervention on AIRg and DI in the total cohort, in neither the high-fat nor LFHCC groups. We observed significant diet*fasting glucose category interactions for AIRg ( P = 0.021) and DI ( P = 0.001) in the high-fat groups. In subjects with normal fasting glucose and preserved first phase insulin secretion, the HMUFA diet increased, whereas the HSFA diet reduced AIRg ( P = 0.015) and DI ( P = 0.010). Conclusions: The effects of dietary fat modification on insulin secretion were minor, and only evident in normoglycemic subjects. In this case, the HMUFA diet improved AIRg and DI, as compared to the HSFA diet.